Spirituality As a Resource of Family Virtue and Well-Being: Religion Diversity Perspectives - Anganthi, Nisa Rachmah Nur (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2016)
This article described about the research findings that there were similar and diverse views of family virtue and well-being from Christian and Islamic perspectives. The research aimed to explore about virtue and well-being values in family life from Christian and Islamic perspectives. The research used qualitative approach as its research method. The respondents were administrative and educative staffs in the higher education institutions based on the spiritual-religion in Yogyakarta and Central Java. The data were collected by semi-structured interview and data documentation. The data were analyzed by its content with phenomenological analysis. The results showed that there were similar and diverse views especially about virtue and well-being through "self; others; and family life". It could be concluded that Christian and Islamic perspectives had similarities in whole worldview and conversely, they had different views in beyond view and divine matter. The implication for these diverse views was that Christian and Islamic adherents could cooperate together in human relation activity and human life.